(untitled) (Journal of humanities and social sciences exploratio, 2026)
With the acceleration of the modernization process of the national governance system and governance capacity, grassroots governments, as the "nerve endings" of national governance, have governance effectiveness that directly relates to the vital interests of the people and the stability of the overall social situation.However, for a long time, influenced by the traditional bureaucratic system and the "fragmented" management model, grassroots government governance has generally faced the "fragmentation" dilemma characterized by overlapping functions, unclear responsibilities and powers, dispersed resources, and fragmented services.Holistic Governance theory, as a reflection and transcendence of the "fragmentation" problems in New Public Management, emphasizes building a seamless, collaborative, citizen-centered service-oriented government through cross-departmental coordination, process integration, and technological empowerment, providing a highly valuable theoretical framework to solve grassroots governance challenges.This paper takes Holistic Governance theory as the core analytical perspective, explaining the core essence of the theory and its intrinsic alignment with grassroots governance innovation; it deeply analyzes the specific manifestations of the current "fragmentation" dilemma in grassroots government governance in China and its underlying generative mechanisms,On this basis, by analyzing cutting-edge practical cases of grassroots governance innovation under the background of digital transformation, it explores the technological implementation paths of holistic governance;Focusing on four dimensions: reshaping value concepts, reorganizing organizational structure, optimizing operational mechanisms, and integrating service supply, it constructs an innovative path and guarantee system for China’s grassroots governments to advance towards holistic governance,with the aim of providing theoretical references and practical guidance for improving the modernization level of grassroots governance.